Analysis of symptomatic recurrences of common bile ducts stones after endoscopic removal: Factors related to early or multiple recurrences. Issue 3 (21st January 2022) - Han, Soo Jeong; Chang, Jae Hyuck; Gweon, Tae-Geun; Kim, Tae Ho; Kim, Hyung-Keun; Kim, Chang Whan
Abstract : Abstract: Early or multiple recurrences of symptomatic common bile duct (CBD) stones are troublesome late complications after endoscopic stone removal. We aimed to determine the factors related to early or multiple recurrences of CBD stones. We retrospectively analyzed patients who underwent endoscopic CBD stone extraction in a single institute between January 2006 and December 2015. Patients were divided into 2 groups according to the number and interval of CBD stone recurrences: single versus multiple (≥2) and early (<1.5 years) versus late (≥1.5 years) recurrence. After exclusion, 78 patients were enrolled and followed up for a median of 1974 (IQR: 938–3239) days. Twenty-seven (34.6%) patients experienced multiple recurrences (≥2 times), and 26 (33.3%) patients experienced early first recurrence (<1.5 years). In the multivariate analysis, CBD angulation was independently related to multiple CBD stone recurrence (OR: 4.689, P  = .016), and endoscopic papillary large balloon dilation was independently related to late first CBD stone recurrence (OR: 3.783, P  = .025). The mean CBD angles were more angulated with increasing instances of recurrence (0, 1, 2, 3, and ≥4 times) with corresponding values of 150.3°, 148.2°, 143.6°, 142.2°, and 126.7°, respectively ( P  = .011). The period between the initial treatment and first recurrence was significantly longer than the period between the first and second recurrence ( P  = .048). In conclusion, greater CBD angulation is associated with the increased number of CBD stone recurrence, and EPLBD delays the recurrence of CBD stones after endoscopic CBD stone removal.